COLOR CONCEPTS IN WARDROBE PLANNING - Tewari, Kirti (International Journal of Research -GRANTHAALAYAH, 2014)
Fashion trends point out colors to wear but individuality should never be overlooked An impression of fine colors in dress will be gained if they are becoming to the person who is to wear them, if they are right for the occasion and if they are selected and arranged so as to make a pleasing ensemble.The larger the area the duller a color should be specially for business wear, but foe an evening or sports wear, it should be modified. The colors should be bright then, provided the wearer is not too large.The colors, in a costume, should be so distributed that a balance is achieved. When the top is light, the other part may be dark but the darkness should be present in the lighter area as a contrast. One should always keep in mind that the wearer should be the centre of interest and the costume a background.In order that the costume may be beautiful its color should be balanced or keyed and the entire color scheme should be related to the coloring of the individual.The aim in choosing colors for individual types should be to select those which will bring out the persons best points and subdue the less attractive ones.